2011
DOI: 10.4173/mic.2011.1.3
|View full text |Cite
|
Sign up to set email alerts
|

nalysis, Modeling and Simulation of Mechatronic Systems using the Bond Graph Method

Abstract: The Bond Graph is the proper choice of physical system used for: (i) Modeling which can be applied to systems combining multidisciplinary energy domains, (ii) Analysis to provide a great value proposition for finding the algebraic loops within the system enabling the process of troubleshooting and eliminating the defects by using the proper component(s) to fix the causality conflict even without being acquainted in the proper system, and (iii) Simulation facilitated through derived state space equations from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…In the bond graph method, power consists of two variables, which are known as the generalized effort and generalized flow and are denoted by e and f , respectively. 18 The power flowing into a bond is defined as the product of an effort variable and a flow variable. In Figure 4, the f i (i=1-4) are the flow variables of each bond and the e i (i=1-4) are the effort variables of each bond; u 1 and u 2 are a pair of Boolean variables, which determine the work state of the corresponding bond.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bond graph method, power consists of two variables, which are known as the generalized effort and generalized flow and are denoted by e and f , respectively. 18 The power flowing into a bond is defined as the product of an effort variable and a flow variable. In Figure 4, the f i (i=1-4) are the flow variables of each bond and the e i (i=1-4) are the effort variables of each bond; u 1 and u 2 are a pair of Boolean variables, which determine the work state of the corresponding bond.…”
Section: Modelingmentioning
confidence: 99%
“…Besides, models such as friction, clearance, and load distribution of threads based on bond graph theory are highly efficient and scalable. 15 Karam and Mare 16 developed an accurate model based on the bond graph approach to simulate the mechanical power transmission within inverted PRSM EMAs, thereby directing particular attention to friction, compliance, and inertia effects. Their paper focused on a system-level model of the mechanical power transmission in an inverted PRSM EMA.…”
Section: Introductionmentioning
confidence: 99%
“…The common methods to analysis the hydraulic pump are analytic method [17,18], state space method [19], and bond graph method [20]. In this paper, the analytic method is used to build the dynamic model of the load sensing pump.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…However, in some cases, the derivation process of certain kind mathematical model of the system is slightly burdensome. Because of the capability of circuit network modeling methodology in directly obtaining the mathematical model in format of transfer function of the circuit system by observing the circuit diagram, and the simplicity of bond graph method in depicting the bond graph of thermal system, in addition with the achievement of successful conversion of different system elements with the same characteristics as shown in reference [10], it becomes very convenient for us to firstly depict the bond graph of thermal system, then transform it into its equivalent circuit diagram, and ultimately derive the mathematical model of thermal system by utilizing circuit network modeling methodology and vice versa. Furthermore, it has been demonstrated that the aforementioned modeling method can also be applied to the modeling of mechanical translation system [11], mechanical rotation system [12] and hydraulic system [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, reference [3] is about modeling of analogue circuits, reference [4] is about modeling of hydraulic system, references [5][6] are about the pseudo bond graph models of thermal system, references [7][8] introduce some bond graph modeling examples of thermal systems and references [9][10] are about the application of bond graph modeling method in multiple energy domains. All the above studies have illustrated that the bond graph modeling method is a very effective modeling tool.…”
Section: Introductionmentioning
confidence: 99%